Skladbe Vladimirja Lovca
Vladimir Lovec (1922–1992) was a composer and a conductor who also worked as a music critic and a publicist. He finished his studies of composition and conducting at the Academy of Music in Ljubljana under the mentorship of professors Lucijan M. Škerjanc and Danilo Švara respectively. The many carefully planned activities with regard to his 100th birth anniversary show just how strongly he influenced the younger generations of musicians who had the chance of knowing him either as a professor and the principal of the Music School Koper or as a conductor of the Orchestra of the Centre for Music Education Koper for which he wrote his Concertino for Flute and Piano. The Music Collection of the National and University Library preserves the complete legacy of Vladimir Lovec, donated to the Library by his wife Zdenka Lovec and by the Centre for Music Education Koper in 1993. The inventory of the composer’s documentary material is available in the collection Zapuščina skladatelja Vladimirja Lovca, while this digital collection contains the autographs of his original compositions and his music that was published by the Editions of the Society of Slovene Composers.
Vladimir Lovec (1922–1992) was a composer and a conductor who also worked as a music critic and a publicist. He finished his studies of composition and conducting at the Academy of Music in Ljubljana under the mentorship of professors Lucijan M. Škerjanc and Danilo Švara respectively. The many carefully planned activities with regard to his 100th birth anniversary show just how strongly he influenced the younger generations of musicians who had the chance of knowing him either as a professor and the principal of the Music School Koper or as a conductor of the Orchestra of the Centre for Music Education Koper for which he wrote his Concertino for Flute and Piano. The Music Collection of the National and University Library preserves the complete legacy of Vladimir Lovec, donated to the Library by his wife Zdenka Lovec and by the Centre for Music Education Koper in 1993. The inventory of the composer’s documentary material is available in the collection Zapuščina skladatelja Vladimirja Lovca, while this digital collection contains the autographs of his original compositions and his music that was published by the Editions of the Society of Slovene Composers.